The Impact of Energy Intensity, Renewable Energy, and Financial Development on Green Growth in OECD Countries: Fresh Evidence Under Environmental Policy Stringency - Nur, Tugba; Topaloglu, Emre E.; Yilmaz-Ozekenci, Sureyya; Koycu, Erol (Mdpi, 2025)
This study examines the impact of financial development, renewable energy, energy intensity, and stringent environmental policies on green growth in twenty-three Organization for Economic Cooperation and Development countries from 2000 to 2023. Additionally, it examines how stringent environmental policies moderate the link between financial development and green growth. Economic complexity, trade openness, and green technology variables are also included in the model as control variables. The index is constructed using economic growth, education, health, CO2 emissions, net forest, and mineral components for green growth, the main variable explained in the research. The Fully Modified Ordinary Least Squares method is applied to estimate elasticity coefficients in the study. The findings show that financial development and energy intensity have a negative impact on green growth, whereas strict environmental policies and renewable energy support green growth. Moreover, the interaction between financial development and stringent environmental policies promotes green growth. At the same time, the control variables of trade openness and economic complexity have a negative impact on green growth, while green technology makes a positive contribution. Furthermore, financial development and energy intensity have the most significant quantitative impact on green growth, while trade openness and stringent environmental policies have the least impact. In line with these findings, environmentally friendly financial instruments and green investments should be supported instead of directing financial resources only to industry-intensive sectors in Organization for Economic Cooperation and Development countries. In this context, implementing energy efficiency policies and increasing incentives for renewable energy are of great importance.
Keywords: financial development; energy economics; green growth; green technology; sustainable development; OECD countries